2015
DOI: 10.1063/1.4936243
|View full text |Cite
|
Sign up to set email alerts
|

A direct evidence of allocating yellow luminescence band in undoped GaN by two-wavelength excited photoluminescence

Abstract: The behavior of below-gap luminescence of undoped GaN grown by MOCVD has been studied by the scheme of two-wavelength-excited photoluminescence. The emission intensity of shallow donor to valence band transition (IOX) increased while intensities of donor-acceptor pair transition and the Yellow Luminescence band (YLB) decreased after the irradiation of a below-gap excitation source of 1.17 eV. The conventional energy schemes and recombination models have been considered to explain our experimental result but on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…AGE power density dependence of the normalized PL intensity (I N ) for samples A and B.increases which results in higher BGE effect due to the enhancement of the non-radiative recombination. Similar AGE density dependence of the I N was observed in our previous studies of TWEPL[22] [25][26] [27].…”
supporting
confidence: 88%
See 1 more Smart Citation
“…AGE power density dependence of the normalized PL intensity (I N ) for samples A and B.increases which results in higher BGE effect due to the enhancement of the non-radiative recombination. Similar AGE density dependence of the I N was observed in our previous studies of TWEPL[22] [25][26] [27].…”
supporting
confidence: 88%
“…The rate equations of the two levels model as shown in Figure 5 can be written below with charge neutrality condition (CNC) [22] ( ) For simplicity, we assumed that the electron capture coefficient C n1 is equal to radiative recombination coefficient B, as 1.2 × 10 −11 cm 3 •s −1 for GaN [32]. Such consideration has been taken by other researchers [26] [33]. Reshchikov et al [1] [34] have reported that the hole capture coefficient of C p1 is in the order of 10 −6 cm 3 •s −1 for GaN.…”
Section: Rate Equation Analysismentioning
confidence: 99%
“…Combination of experimental intensity change as a function of the BGE density with the rate equation analysis of trap filling effect based on the SRH statistics enabled us to open a way of determining CR parameters quantitatively as the scheme of two‐wavelength excited photoluminescence (TWEPL) . Detection and investigation of CR levels have already been reported for different types of semiconductors like GaAs/AlGaAs QWs , GaN/InGaN QWs , AlGaN QWs , GaN , GaP 1− x N x , and Ba 3 Si 6 O 12 N 2 :Eu 2+ phosphors .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in the HVPE growth process, the Si impurity will be introduced by the quartz reactor tube and trapped around the dislocations. Moreover, the YL band is believed to be related to the deep states (located at~1 eV above the valence band) [6]; in particular, it is assumed to be the result of a donoreacceptor pair recombination from a shallow donor to a deep acceptor in undoped GaN [19,35]. Based on the above understandings, we consider that in our high-quality FS GaN, the Si donors around the dislocations, which are reasonable sources of shallow donors, will recombine with potential deep acceptors (V Ga ) and finally respond with the YL.…”
Section: Resultsmentioning
confidence: 99%